Cover Picture: A Polymorphic Azobenzene Cage for Energy‐Efficient and Highly Selective p‐Xylene Separation (Angew. Chem. Int. Ed. 48/2020). Issue 48 (13th October 2020) - Moosa, Basem; Alimi, Lukman O.; Shkurenko, Aleksander; Fakim, Aliyah; Bhatt, Prashant M.; Zhang, Gengwu; Eddaoudi, Mohamed; Khashab, Niveen M.
Abstract : A stable and recyclable non‐porous azobenzene‐based organic cage (AZO‐Cage) that exhibits exclusive selectivity towards p ‐xylene ( p X) compared to all C8 isomers is reported by N. M. Khashab and co‐workers in their Communication on page 21367 . This AZO‐Cage undergoes a crystal‐to‐crystal phase transition selectively in the presence of p X in both the liquid and vapor phase, which makes this platform ideal for eventual translation for the separation of high‐value benzene derivatives. The cover image illustrates the host cage crystal transition in the presence of p X guest molecules.